2015
DOI: 10.1074/jbc.m115.663666
|View full text |Cite
|
Sign up to set email alerts
|

FANCD2-associated Nuclease 1, but Not Exonuclease 1 or Flap Endonuclease 1, Is Able to Unhook DNA Interstrand Cross-links in Vitro

Abstract: Background:We studied how the endo/exonucleases EXO1, FAN1, and FEN1 process substrates resembling replication forks blocked by interstrand cross-links (ICLs). Results: All three enzymes cleaved off the single-stranded 5Ј flap, but FAN1 was also able to incise the substrate behind the ICL. Conclusion: FAN1 can unhook ICLs. Significance: In vivo, FAN1 may not require a 3Ј flap nuclease to unhook ICLs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
0
36
0
Order By: Relevance
“…Recently, in vitro biochemical analyses of SLX4/FANCP-and XPF/ FANCQ-dependent processing of the cross-links and the ICL unhooking studies from Xenopus egg extracts strongly support the major involvement of the 3 ′ flap endonuclease activity of XPF/FANCQ in initiating and completing ICL incisions (Douwel et al 2014;Hodskinson et al 2014). However, it is evident from the published biochemical work and our unpublished data that FAN1, through its endonuclease and exonuclease activities, is able to incise and completely unhook different types of cross-link substrates in vitro (Zhao et al 2014;Pizzolato et al 2015;A Wang, L Timashev, and A Smogorzewska, unpubl.). The discrepancy may come from the fact that FAN1 may be involved at stalled forks that do not look like the divergent replication forks formed on plasmids in the Xenopus egg extracts or that FAN1 predominantly works in G1 and not in S phase.…”
Section: Fan1 Vs Other Nucleasesmentioning
confidence: 59%
See 2 more Smart Citations
“…Recently, in vitro biochemical analyses of SLX4/FANCP-and XPF/ FANCQ-dependent processing of the cross-links and the ICL unhooking studies from Xenopus egg extracts strongly support the major involvement of the 3 ′ flap endonuclease activity of XPF/FANCQ in initiating and completing ICL incisions (Douwel et al 2014;Hodskinson et al 2014). However, it is evident from the published biochemical work and our unpublished data that FAN1, through its endonuclease and exonuclease activities, is able to incise and completely unhook different types of cross-link substrates in vitro (Zhao et al 2014;Pizzolato et al 2015;A Wang, L Timashev, and A Smogorzewska, unpubl.). The discrepancy may come from the fact that FAN1 may be involved at stalled forks that do not look like the divergent replication forks formed on plasmids in the Xenopus egg extracts or that FAN1 predominantly works in G1 and not in S phase.…”
Section: Fan1 Vs Other Nucleasesmentioning
confidence: 59%
“…In some cases, the processing of crosslink substrates by FAN1 occurred at both the 5 ′ and 3 ′ sides of the cross-link, leading to complete unhooking of the DNA cross-link (Wang et al 2014;Pizzolato et al 2015). To date, SNM1A, a homolog of yeast Pso2, is the only other known ICL-processing nuclease that is capable of digesting past the ICL, leading to the insight that FAN1 may be functionally redundant with SNM1A in DNA ICL repair.…”
Section: Fan1 Deficiency Can Be Partially Compensated For By Snm1amentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the FAN1 nuclease has also been demonstrated to act in an exo‐like fashion and is able to degrade past and release DNA substrates containing ICLs (Wang et al , 2014; Zhao et al , 2014; Pizzolato et al , 2015). Moreover, studies in fission yeast and more recently in mouse cells imply that FAN1 and SNM1A may play a redundant role in ICL repair, or contribute to different ICL repair sub‐pathways (Fontebasso et al , 2013; Thongthip et al , 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies showed that human FAN1 can degrade ICL-containing oligonucleotides past the lesion in replication-like intermediates, thereby unhooking the ICLs (32)(33)(34).…”
Section: Dna Synthesis (Tls) and The Second Strand Is Repaired By Hommentioning
confidence: 99%